Internalization of character values in the Qur'an in order to overcome the problem of Gen “Z ” characters - Imam Hanafi; Ach Puniman; Anita Anita; Anni Annisa (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research aims to identify the problems of the Gen Z generation and to overcome their problems with the character values in the al-Qur'an. This type of research is library research obtained from various journal articles and proceedings on Google Scholar. Its analysis techniques were conducted in four stages, namely: data collection, data classification, data display, conclusion. Its results reveal that there are three important elements that play roles in shaping the character values of the al-Qur'an in the generation, including family, school and society. The internalization strategy can be applied to three elements in the form of: exemplary (showing good character), advisory education, supervisory education, knowledge and understanding, and habituation.